2022
DOI: 10.3390/healthcare10101873
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Players Involved in Overkill: An Analysis of 71 Cases in Central Italy

Abstract: “Overkill” is characterized by the finding of excessive wounds on the victim’s body. Despite the large use of this term, it does not have a definition in the literature yet. Our study aimed to analyze the information related to the dynamics of overkill cases, collecting objective variables, and producing a profile of the players involved in this type of homicides. Data on 71 overkill cases from reports of the autopsies performed in the Section of Legal Medicine of the University of Rome Tor Vergata from 1 Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…As known, autopsy findings can provide significant forensic evidence, potentially confirming or refuting hypotheses about the circumstances of familicide [14]. Our study demonstrated a high level of severity of victim injuries, with the predominant number of injuries per victim being about 12, confirming that familicide is often characterized by overkill, signifying intense anger or rage [11,15,16]. From this count, asphyxiation and fire burns were excluded, as they are less frequent, but this may hint at the nature of the event, the level of planning involved, and the offender's state of mind [10].…”
Section: Discussionsupporting
confidence: 68%
“…As known, autopsy findings can provide significant forensic evidence, potentially confirming or refuting hypotheses about the circumstances of familicide [14]. Our study demonstrated a high level of severity of victim injuries, with the predominant number of injuries per victim being about 12, confirming that familicide is often characterized by overkill, signifying intense anger or rage [11,15,16]. From this count, asphyxiation and fire burns were excluded, as they are less frequent, but this may hint at the nature of the event, the level of planning involved, and the offender's state of mind [10].…”
Section: Discussionsupporting
confidence: 68%
“…Whether or not there is a relationship between the modus operandi (the way a person acts) and the cause of death of the victim can be known if an autopsy is performed on the victim's body. Clarity on whether or not there is a relationship between the modus operandi and the cause of death is an urgent matter to be used as evidence in court (Bakhtiar et al, 2019;Flora, 2019;Solarino et al, 2019;Tavone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%